Authenticity and spirituality (Bulletin KNOB, 2010)
According to Seung The Charter of Venice (1964) was presented as a universal declaration in the field of protection of monuments and historic buildings, but in reality it was steeped in a European spirit. Consequently, this charter does not do justice to specifically eastern values. Western culture, as Seung starts his argument, originated from the Greek and Jewish civilizations, whereas eastern culture is based on China.There are great differences between these two worlds, but they are nevertheless ignored by the charter referred to, which was based on the range of thought of writers such as John Ruskin and Camillo Boito.Even if Seung were right in his essentialist proposition with respect to Chinese culture, this is not sufficient proof of the fact that western culture is materialist. Nor is it clear yet why the charter of 1964 would have to comply with the image given of Chinese culture by Seung. A charter brings up something that needs improvement, it has not been developed to comply with traditions.